The Memoirs of Jacques Casanova de Seingalt, 1725-1798. Volume 19: Back Again to Paris - Casanova, Giacomo, 1725-1798; Machen, Arthur, 1863-1947 (Salt Lake City, UT : Project Gutenberg, 2004)
"The Memoirs of Jacques Casanova de Seingalt, 1725-1798. Volume 19: Back Again..." is part of an 18th-century memoir written in French by Venetian adventurer Giacomo Casanova. This installment continues Casanova's legendary autobiography, which spans twelve volumes and chronicles his life through 1774. Originally censored and mistranslated for over a century, the work reveals the intimate adventures of one of history's most famous libertines. The manuscript's remarkable journey$1 (Bfrom Casanova's deathbed to a French library's record-breaking acquisition$1 (Bmirrors the dramatic life contained within its pages. (This is an automatically generated summary.)s
Wikipedia page about this book: https://en.wikipedia.org/wiki/Histoire_de_ma_vie
Release date is 2004-12-11
Produced by David Widger
Keywords: Casanova, Giacomo, 1725-1798; Europe -- History -- 18th century -- Biography